Rozwiązane

1. Rozwiąż:
a) | 3 - 2x | = 1
b) | x + 5 | > 4
2. Usuń niewymierność z mianownika:
7 / 5 - √2
3. Wykonaj działania wraz z uproszczeniem:
(3x + 5)(4 - 2x)
4. Znajdź AuB, A∩B, A\B, B\A, jeśli:
a) A = { x ε Z : | x | ≤ 2 } B = { 1,2,3 }
b) A = ( -2, 3 ) B = { x ε R : x + 1 ≥ 2 }



Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

a) 3-2x=1  -2x=-2 x=1

3-2x=-1  -2x=-4 x=2

b) x∈(-∞,-9) x∈(-1.∞)  

x+5>4      x>-1

x+5<-4     x<-9

2.) 7(5+√2)/23

3.

12x -6[tex]x^{2}[/tex] +20 -8x= -6

4.a) |x|=≤2

x>=-2 x≤ 2 Całkowite to -2 -1 0 1 2

A={-2,-1,0,1,2}  B = { 1,2,3 }

AuB= {-2,-1,0,1,2}

A∩B= {1,2}

B\A= {3}

b)

x+1≥2

x≥1

A = ( -2, 3 )

B= <1.∞)

AuB=(-2,∞)

A∩B=(1,3)

B\A= (3,∞)